Nonlinear differential equations in wavelet bases - Cattani, C.; Pecoraro, M. (Інститут гідромеханіки НАН України, 2000)
In this paper we discuss the problem of finding numerical solution of some nonlinear differential equations using wavelet bases. It is also given a short outline of the method in dealing with the nonlinear heat equation.